Early Childhood Caries and Its Management Strategies - A Review - K S, VIKRAMAN; T, LAKSHMI; S, KAVITHA (The journal of contemporary issues in business and government, 2021)
The aim of the review is to update the current data about Early childhood caries (ECC) and its etiology, prevalence, risk factors, management, and preventive strategies. Dental caries is an international public health challenge, especially amongst young children. Early childhood caries is a serious public health problem in both developing and industrialized countries. ECC can begin early in life, progresses rapidly in those who are at high risk, and often goes untreated. ECC can be a particularly virulent form of caries, beginning soon after dental eruption, developing on smooth surfaces, progressing rapidly, and having a lasting detrimental impact on the dentition. Preventing and controlling the development of ECC among children is important to maintain effective eating, speech development, and formation of a positive self-image.